Strategi Masyarakat Pesisir dalam Mempertahankan Pembuatan Atap Rumpia di Kalangan Masyarakat Modern di Lingga - Titin Marliani; Marchilina Marchilina; Jasmin Miluwanti (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2022)
Among the coastal communities of Lingga Island, precisely in Linau Village, the wife works as a roof maker from rumbia to meet their daily needs, making roofs from thatch is of great interest to the coastal community. However, there are still some of the coastal communities who still use the roof of the lumbia due to the community's own interest in thatch roof. This research was carried out in Lingga Regency, Riau Islands, precisely in Linau village, the population of this study were all thatched roof craftsmen, the authors used direct communication techniques to thatched craftsmen (interviews), with the consideration that the location is a place for making thatch roof crafts in the area. Linau Village, where the activities of women in this coastal area are roofing craftsmen from thatch to help the family economy. The population of this research is all the people who work as thatched roofing craftsmen in Linau Village, totaling 5 thatch roof craftsmen. Our work shown that the marketing area for thatched roof craftsmen is in the village of Linau (Semarug) which is very diverse, starting from the shape and price. There are only marketing around the village of Linau village and some outside the village of Linau village, but none of the six craftsmen have been able to sell or market thatch roofing products outside the city. But almost all villages in Lingga are the marketing destinations of thatched roofs. Where these craftsmen have a common goal and a common interest in the marketing of thatched roofs where their goal is to preserve the heritage of their ancestors that has existed since time immemorial.